Editorial - Engelbrecht, LK (Social Work/Maatskaplike Werk, 2023)
This first edition in 2023 of Social Work/Maatskaplike Werk offers themes that centre on social work with persons affected by substance use disorders, on environmental social work and social work with children. The latter theme focuses on specialist areas concerning parents of children suffering from hearing loss, social assistance to orphaned children, foster care, ethical guidelines for adoption, grandparent-grandchildren care and child participation.